The Effectiveness of Single‐Sex Schools through Out‐of‐School Activities: Evidence from South Korea. (22nd October 2018) - Hahn, Youjin; Wang, Liang Choon
Abstract: Students' out‐of‐school activities and time use can play a crucial role in facilitating the effect of schools on students' achievement. Using data from Seoul, South Korea, where students are randomly assigned into schools, we show that when single‐sex schools improve students' test performance, their effect is positive on students' time spent on study‐related out‐of‐school activities. Our results indicate that out‐of‐school activities explain roughly 21%–30% of the effect of single‐sex schooling on test performance.